Pengaruh Budaya Kerja, Komitmen Pegawai dan Dukungan Organisasi Terhadap Produktifitas Kerja Pegawai Biro Administrasi Sekeretariat Daerah Provinsi DKI Jakarta - zaman zaini; Mughni Hakim; Hasim A. Abdullah (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The problem that is often faced by organizations in achieving their goals is the low productivity of their employees. The problem about work productivity is a common problem that occurs in every organization. Work productivity shows the level of ability of employees to achieve results (ouput), especially in terms of quantity, therefore the level of productivity of each employee can be different. This study aims to analyze the influence of work culture, employee commitment and organizational support, both partially and simultaneously, on the work productivity of employees of the DKI Jakarta Provincial Secretariat. This research was conducted by questionnaire survey method which was distributed to 67 respondents who were employees of the Regional Secretariat of DKI Jakarta Province. The number of samples in this study were 67 people with the sampling technique used was total sampling. The analysis used in this study is correlation and regression, t test, F test and test coefficient of determination. The results of the study prove that organizational culture and commitment of employees have a strong influence on employee work productivity, while organizational support has a moderate effect on employee work productivity. Taken together, the three independent variables have a very strong influence on the work productivity of employees of the DKI Jakarta Provincial Secretariat Administration Bureau. The results of the analysis show that these three variables are very dominant factors that influence employee work productivity.